Pathogenicity, Mycotoxin Production, and Control of Potato Dry Rot Caused by Fusarium spp.: A Review - Huali Xue; Qili Liu; Zhimin Yang (Journal of Fungi, 2023)
Fusarium dry rot is one of the major potato diseases during storage after harvest, which not only results in quality degradation but also causes great economic losses. The disease can be elicited by some species of Fusarium, and the pathogenic fungi of Fusarium causing potato dry rot are considerably diverse in various countries and regions. The disease caused by Fusarium spp. is associated with mycotoxins accumulation, which has phytotoxic and mycotoxic effects on humans and animals. Chemical synthetic fungicide is considered the main control measure for the Fusarium dry rot of potato; nevertheless, it is unfortunate that persistent application inevitably results in the emergency of a resistant strain and environmental contamination. A comprehensive disease control strategy includes potato cultivar selection, appropriate cultural practices (crop rotation, cultivate pattern, fertilization, and irrigation), harvesting processes and postharvest treatments (harvesting, classification, packaging, wound healing), and storage conditions (environmental disinfection, temperature, humidity and gas composition) along with the application of fungicide pre-harvest or post-harvest. Recently, emerging studies have indicated that eco-friendly strategies include physical control, chemical methods (such as the application of generally-recognised-as-safe (GRAS) compounds or chemical (elicitors) and biological control have been introduced to combat the Fusarium dry rot of potato.